2012
DOI: 10.1080/15298868.2011.616000
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between Performance and Life Satisfaction: The Moderating Role of Passion

Abstract: The dualistic model of passion (Vallerand, 2010) regards passion as a strong inclination toward a self-defining activity that one loves, values, and in which one invests a substantial amount of time and energy. The model proposes two distinct types of passion, harmonious and obsessive, that predict adaptive and less adaptive outcomes, respectively. It was hypothesized that individuals with an obsessive passion would have their life satisfaction dependent on their performance. This is so because obsessive passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 39 publications
3
64
0
3
Order By: Relevance
“…Finally, other studies in this initial research have also shown that obsessive (but not harmonious) passion correlated to rigid persistence in ill-advised activities ( Vallerand et al ,Studies 3 and 4). Of interest is the fact that the above fi ndings obtained with the Passion Scale have been replicated in several studies using experimental inductions of the two types of passion (see Bélanger, Lafrenière, Vallerand, & Kruglanski, 2013 ;Lafrenière, Vallerand, & Sedikides, 2013 ). Overall, these results provide important support for the conceptual validity of the two types of passion and their divergent effects on various outcomes.…”
Section: Initial Research On the Concept Of Passion And The Dmpmentioning
confidence: 54%
“…Finally, other studies in this initial research have also shown that obsessive (but not harmonious) passion correlated to rigid persistence in ill-advised activities ( Vallerand et al ,Studies 3 and 4). Of interest is the fact that the above fi ndings obtained with the Passion Scale have been replicated in several studies using experimental inductions of the two types of passion (see Bélanger, Lafrenière, Vallerand, & Kruglanski, 2013 ;Lafrenière, Vallerand, & Sedikides, 2013 ). Overall, these results provide important support for the conceptual validity of the two types of passion and their divergent effects on various outcomes.…”
Section: Initial Research On the Concept Of Passion And The Dmpmentioning
confidence: 54%
“…Although much research has focused on the effects of emotions in creativity, few studies have addressed the source of these emotions and their role during a successful creative process. Findings from a recent study with professional painters (Lafrenière, St-Louis, Vallerand, & Donahue, 2012, Study 1) revealed that they are highly passionate for their craft. In addition, being passionate entails being emotionally charged toward an activity, and research has shown that the experience of emotions is intensified during and after engaging in the passionate activity (see Vallerand, 2008Vallerand, , 2010 in press for reviews).…”
mentioning
confidence: 92%
“…The voluntary and personal endorsement of work as an important part of one's life is conducive to positive experiences, because the employee is able to be fully engrossed in work when necessary, but they experience no guilt when they are not fully engrossed, whether at work or at home (Lafrenière, St-Louis, Vallerand, & Donahue, 2012;Vallerand, 2012). The overall positive experience of balancing work and leisure in a meaningful way should relate positively to life satisfaction.…”
Section: Passion For Work and Wellbeingmentioning
confidence: 99%